2018
DOI: 10.1371/journal.pone.0192871
|View full text |Cite
|
Sign up to set email alerts
|

Predicting species emergence in simulated complex pre-biotic networks

Abstract: An intriguing question in evolution is what would happen if one could “replay” life’s tape. Here, we explore the following hypothesis: when replaying the tape, the details (“decorations”) of the outcomes would vary but certain “invariants” might emerge across different life-tapes sharing similar initial conditions. We use large-scale simulations of an in silico model of pre-biotic evolution called GARD (Graded Autocatalysis Replication Domain) to test this hypothesis. GARD models the temporal evolution of mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 75 publications
0
21
0
Order By: Relevance
“…It turns out that the definition of cores/compartments fully overlaps with that of composomes (see §8), as has actually been explicitly stated in another paper by the same authors [ 27 ]. These cores/compartments are identical to what in graph theory is called communities, whose relevance to GARD is discussed in §8 and in [ 92 ].…”
Section: Gard Evolutionmentioning
confidence: 88%
See 2 more Smart Citations
“…It turns out that the definition of cores/compartments fully overlaps with that of composomes (see §8), as has actually been explicitly stated in another paper by the same authors [ 27 ]. These cores/compartments are identical to what in graph theory is called communities, whose relevance to GARD is discussed in §8 and in [ 92 ].…”
Section: Gard Evolutionmentioning
confidence: 88%
“…With such a modification, most randomly formed GARD compositional assemblies will not be RAF. On the other hand, as the compounds belonging to a composome show overlap with communities within the β -matrix-defined subsets of more tightly linked network nodes [ 27 , 92 ] (see §8), it follows that composomes are much more likely to be RAFs. If true, GARD kinetic simulations could be used, in parallel to the published analytic algorithm [ 73 ], to distinguish between RAFs and non-RAFs.…”
Section: Replicating Composomesmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, model parameters could be safely ignored while still being able to robustly predict the best simulator to use. More recently, it has been demonstrated that a similar approach (namely focussing on structure and ignoring parameters) was sufficient to predict the outcome of long stochastic chemical simulations Markovitch and Krasnogor (2018). Thus, we follow a similar approach here and focus solely on model structure and ignore model parameters for the purpose of predicting the speed at which different model checkers verify system level models.…”
Section: Methodsmentioning
confidence: 99%
“…We show numerically, and by simulating many cases, that this yields multistationarity or multistability (Figure e), i. e., multiple stable steady‐state solutions (see formal mathematical definitions by Joshi and Shiu), where the specific points of convergence depend on the efficiency of each replicator and the system's initial conditions. As shown in various numerical studies of replication networks, the current system also displays patterns of behavior that are difficult to predict without simulation. Furthermore, the simulations reveal fundamental trends and characteristics potentially useful for design of future experiments.…”
Section: Introductionmentioning
confidence: 95%